2012
DOI: 10.1371/journal.pgen.1002833
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Fatty Acid Transport Protein Regulates Rhodopsin-1 Metabolism and Is Required for Photoreceptor Neuron Survival

Abstract: Tight regulation of the visual response is essential for photoreceptor function and survival. Visual response dysregulation often leads to photoreceptor cell degeneration, but the causes of such cell death are not well understood. In this study, we investigated a fatty acid transport protein (fatp) null mutation that caused adult-onset and progressive photoreceptor cell death. Consistent with fatp having a role in the retina, we showed that fatp is expressed in adult photoreceptors and accessory cells and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 46 publications
2
72
0
Order By: Relevance
“…We therefore tested Fatp , the fly homolog of FATP1 (SLC27A1) and FATP4 (SLC27A4) (Dourlen et al, 2012; Dourlen et al, 2015). Finally, we assessed the function of various apolipoproteins that belong to the lipocalin family (Hauser et al, 2011; Kalaany and Mangelsdorf, 2006), such as glaz and nlaz .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore tested Fatp , the fly homolog of FATP1 (SLC27A1) and FATP4 (SLC27A4) (Dourlen et al, 2012; Dourlen et al, 2015). Finally, we assessed the function of various apolipoproteins that belong to the lipocalin family (Hauser et al, 2011; Kalaany and Mangelsdorf, 2006), such as glaz and nlaz .…”
Section: Resultsmentioning
confidence: 99%
“…These proteins are localized to the ER and plasma membrane in vertebrate cells (Stahl, 2004). Drosophila Fatp is expressed in both neurons and glia (Dourlen et al, 2012) and is most similar to mammalian FATP1 and FATP4 (Dourlen et al, 2015). We reduced expression of Fatp in neurons and glia and ascertained that these manipulations do not affect PR morphology immediately after eclosion (Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous Drosophila studies on fatp mutants reported metabolic and eye-specifi c phenotypes ( 32,33 ) but did not discriminate between FAtransporter or ACS activities. Importantly, our observations favor the notion that in the process of CHC synthesis, FATP acts instead through its ACS domain, because fatp knockdown impedes mbCHC synthesis in the oenocytes, and mbCHC precursors are mainly synthetized within the ( Fig.…”
Section: Fa Metabolism In the Fb Affects Chc Biogenesismentioning
confidence: 91%
“…To date, only one mosaic screen has investigated the mechanisms regulating adult PR function, by monitoring the visual response via electroretinogram recordings 32 . With the Tomato/GFP-FLP/FRT method and the possibility of performing time course analysis in living mutant animals, we have designed a new method for identifying the factors regulating adult PR viability and function 20,24 .…”
Section: Discussionmentioning
confidence: 99%